Facile Preparation of Biocomposite from Prawn Shell Derived Chitosan and Kaolinite-Rich Locally Available Clay - Shanta Biswas; Taslim U. Rashid; Abul K. Mallik; Md. Minhajul Islam; M. Nuruzzaman Khan; Papia Haque; Mala Khan; Mohammed Mizanur Rahman (International Journal of Polymer Science)
A novel composite material was prepared from prawn shell derived chitosan (CHT) and locally available kaolinite-rich modified Bijoypur clay (MC) using a facile technique in which dilute acetic acid was used as a solvent for dissolving chitosan and composite fabrication whereas distilled water was used for preparing the clay dispersion. Bijoypur clay mainly consists of kaolinite clay mineral and it was modified with the dodecyl amine to make it organophilic. Morphology and properties of the composites (different weight ratio of MC and CHT) have been studied and compared with those of pure CHT and MC. Purification and modification of Bijoypur clay were investigated by X-ray diffraction (XRD), X-ray fluorescence (XRF), and Fourier transformed infrared spectroscopy (FTIR) analyses. The fabrication of CHT-MC composites was confirmed by FTIR analysis. Thermogravimetric analysis (TGA) and differential scanning colorimetry (DSC) were used to investigate the thermal stability of the composites. It was observed that dispersed clay improves the thermal stability and enhances the hardness of the matrix systematically with the increase of clay loading. In this study, a better insolubility in both acidic and alkaline media of the composites is also observed compared to pure chitosan.